(untitled) - Nguyễn, Anh Tài (Cần Thơ, 2015)
Investigated the impacts of the use of portfolio on learners writing performance in terms of paragraph components such as content, organization, vocabulary, language and mechanics as well as the learners' attitudes toward of the use of portfolio in the writing learning process
Keywords: English language,Tiếng Anh; Study and teaching,Dạy và học